STRATEGI PENCEGAHAN TRAGEDI HAK ASASI PEREMPUAN - Wahyudin, Ayub (IAIN Pekalongan, 2014)
Abstract: The National women's commission released data annually on violence against women that always increase. Policy advocacy effort and socialization on the elimination of violence against women was held across the archipelago. We need a perfect strategy that involves all stakeholders from academic community, community leaders, public officials, law enforcement authorities, the President and all citizens to unite and suppress the liberation of women from violence and discrimination. The tragedy of human rights including women’s rights is an urgent issue to be dealt with. Abstrak : Komisi perempuan Nasional merilis data setiap tahun tentang kekerasan terhadap perempuan yang selalu meningkat. Upaya advokasi kebijakan dan sosialisasi tentang penghapusan kekerasan terhadap perempuan diadakan di seluruh nusantara. Kita perlu strategi yang sempurna yang melibatkan semua pemangku kepentingan dari civitas akademika, tokoh masyarakat, pejabat publik, aparat penegak hukum, Presiden dan semua warga negara untuk bersatu dan menekan pembebasan perempuan dari kekerasan dan diskriminasi. Tragedi HAM termasuk hak-hak perempuan merupakan isu yang mendesak untuk ditangani.